Low Level of Vitamin D is Correlated with High C-Reactive Protein (CRP) and Disease Activity in Indonesian Juvenile Idiopathic Arthritis (JIA) Patients - Desy Wulandari; Wisnu Barlianto; Tita Luthfia Sari (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Vitamin D plays essential role in the regulation of inflammation, such as in pathogenesis of Juvenile Idiopathic Arthritis (JIA). Vitamin D deficiency has been reported among JIA patients, but there were conflicting results regarding the correlation with disease activity. This study aimed to assess vitamin D serum level and its correlation with C-Reactive Protein (CRP) and disease activity in JIA patients.METHODS: Children who were diagnosed with JIA according to International League of Associations for Rheumatology (ILAR) criterias were enrolled as JIA group subjects, while age and sex-matched healthy children were enrolled as the control group subjects. Vitamin D and CRP serum level were measured. Disease activity of JIA patients was calculated by Juvenile Arthritis Disease ActivityScore-27 (JADAS-27).RESULTS: Vitamin D serum level was lower in the JIA group compared to the healthy control group (p=0.000). Among 26 JIA patients, 61.5% were deficient, 30.8% were insufficient, and 7.7% had normal vitamin D. No significant different in CRP level between vitamin D group (p=0.441), but there was significant different in JADAS-27 (p=0.001). The mean of CRP and JADAS-27 were found highest in vitamin D deficiency group. Vitamin D serum level was negatively correlate with CRP (p=0.021, r=-0.452) and JADAS-27 (p=0.001 r=-0.595).CONCLUSION: Low level of vitamin D in JIA patients was inversely related to higher CRP and disease activity,suggesting that vitamin D supplementation could be havepotential role in JIA treatment.KEYWORDS: vitamin D, CRP, disease activity,JADAS-27, JIA